Implementation of the Pancasila Student Profile Strengthening Project (P5) as an Effort to Improve Environmental Awareness in Elementary School Students - Pertiwi, Hanalia; Wachid Bambang Suharto, Abdul (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research is interesting because it analyzes the implementation of the Pancasila Student Profile Strengthening Project with the theme of a sustainable lifestyle at SDN Pasiraman Kidul to cultivate students' environmental awareness. This study aims to analyze the implementation of the Pancasila Student Profile Strengthening Project with the theme of a sustainable lifestyle at SDN Pasiraman Kidul. This research uses a qualitative approach with a case study. Research data was analyzed using Talcott Parson's structural functional theory with data collection techniques conducted through observation, interviews, and document studies in August 2024. The selection of informants used purposive sampling, meaning that the informants selected had information data that could support the research results, totaling 10 people, including 1 principal, 1 coordinating teacher, 3 facilitator teachers, and 5 students of SDN Pasiraman Kidul. Researchers conducted source triangulation and technique triangulation for data validity. Data analysis techniques referred to the thinking of Miles and Huberman, namely data reduction, data presentation, and conclusion. The results of the study reveal that the achievements in the P5 program in the school environment include the collection of various types of waste, organic waste to be used as a learning medium for making compost, non-organic waste such as mineral water bottle plastic and plastic garbage bags to become ecobricks, and various other recycled crafts. The implementation of the P5 theme of a sustainable lifestyle with the topic